PERBAIKAN SIFAT FISIK DAN KIMIA TANAH ULTISOL SIMALINGKAR B KECAMATAN PANCUR BATU DENGAN PEMBERIAN PUPUK ORGANIK SUPERNASA DAN ROCKPHOSPHIT SERTA PENGARUHNYA TERHADAP PRODUKSI TANAMAN JAGUNG (Zea mays L.) - Evan Sanjaya Sipayung; Gantar Sitanggang; Muhammad M. B Damanik (Jurnal Agroekoteknologi, 2014)
ABSTRACTEvan Sanjaya Sipayung. Repair Soil Physical and Chemical Properties Ultisol Simalingkar BDistrict of Pancur Batu With Organic Fertilizer Provision SUPERNASA and Rockphospit AndIts Effect on Production of Corn(Zea mays L.) Guided By Gantar Sitanggang and M. M. B.Damanik.This study implemented in native land Ultisol Simalingkar Pancur Batu Subdistrict BDeli Serdang regency. This study aims to improve the physical and chemical properties of soilultisol Simalingkar B Deli Serdang regency and its influence on the production of maize (Zeamays L.) with the application SUPERNASA and rockphospit. These data were analyzed by usinga randomized block design (RBD) Factorial.The results showed that the organic fertilizerSUPERNASA can increase the corn production. The rock phosphate significantly increase BD,C-Organic, P-available of soil and corn production.Keywords: Ultisol, SUPERNASA solid organic fertilizer, rockphosphate, corn